Influence of age, season, lactation on haematology and iron biochemistry of crossbred cattle - RANDHAWA, C S; PAL, HEIGO; RANDHAWA, S S; UPPAL, S K (The Indian Journal of Animal Sciences, 2011)
Hematology and iron metabolism profile was determined in crossbred cattle in relation to age, season and lactation. Mean values of PCV and MCV were significantly higher in heifers (1–3 years) and PCV in old (>9 years) cattle. The plasma iron concentration was lowest in heifers. The values of Hb, PCV, TEC, plasma iron and total iron binding capacity were lower in lactating and MCHC was higher in lactating than non-lactating cows. Mean PCV and MCV was high during winter and spring season as compared to summer and rainy season. Mean MCH value was the lowest in rainy season whereas MCHC was the highest in summer. Season did not affect plasma Fe, total iron binding capacity and per cent transferrin saturation. Plasma Fe concentration varied from 87–269.6 μg.dl–1, total iron binding capacity varied widely from 181.6 to 887μg.dl–1 and transferrin saturation from 18.2 to 80% in cattle.